Middle-Late Permian magnetostratigraphy and the onset of the Illawarra Reversals in the northeastern Parana Basin, South America - Aragão, Marcela [UNESP]; Scardia, Giancarlo [UNESP] (Oxford University Press (OUP), 2021)
Recent compilations of the Illawarra Reversals show remarkable differences in the onset age (265 Ma versus 269 Ma) and the magnetic polarity pattern, hampering the establishment of a reference geomagnetic timescale for the Middle-Late Permian. The Parana Basin hosts a 7-km-thick, discontinuous sedimentary succession spanning the Palaeozoic to the Mesozoic, including the Gondwana 1 supersequence which extends from Late Carboniferous to the Triassic or Jurassic. We provide the magnetostratigraphy of the middle and upper Permian part of this sequence of a ca. 300-m-long core, pertaining to the Passa Dois Group and the Piramboia Formation. Sample demagnetization of NRM revealed two magnetic overprints ascribed to the Brunhes chron and to the emplacement of Parana Large Igneous Province in the Early Cretaceous, respectively. Stable, dual polarity characteristic components (ChRM) were isolated at temperatures higher than 450 °C and interpreted as a primary detrital magnetic remanence (DRM), acquired during or soon after sediment deposition. Available U-Pb dating on volcanic zircons from the literature provided independent chronologic constraints for our magnetostratigraphy. A total of 8 reverse polarity intervals were identified, the lowermost of which (up to 110 m thick) correlates to the Kiaman Superchron. The overlying Illawarra is dominated by a reverse polarity magnetization with thin (4-5 m thick) normal polarity intervals. This pattern agrees with the Illawarra sequence from the Karoo Basin and other proposed timescales for the Permian. The onset of the Illawarra reversals is interpolated to ca. 270 Ma, close to the age of 269 Ma from the Karoo Basin. Combined magnetostratigraphy and geochronology yielded sediment accumulation rates of ca. 8 m Myr-1 for the Passa Dois Group in the northeastern (marginal) sector of the Parana Basin, indicating that Serra Alta and Teresina Formations span 279-274 Ma and 274-254 Ma, respectively.
Keywords: Magnetostratigraphy; Palaeomagnetism; South America